Pelatihan Pengembangan Wirausaha Popcorn Bercita Rasa Global - Ivana Wamafma; Westim Ratang (Jurusan Manajemen dan Bisnis Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2022)
This service aims to create processed popcorn corn products with a variety of flavors, take advantage of business opportunities by taking advantage of the abundant garden produce in Koya Koso, and introduce popcorn products to help the family economy. The method used is to conduct training which is attended by the families of corn farmers. The participants who are corn farmers are motivated to develop a popcorn business and want continuous training.